High-performance lithium–sulfur batteries enabled by regulating Li2S deposition. Issue 38 (22nd September 2021) - Lin, Qiaowei; Huang, Ling; Liu, Wenhua; Li, Zejian; Fang, Ruopian; Wang, Da-Wei; Yang, Quan-Hong; Lv, Wei
Abstract : This perspective highlights the significance of regulating Li2 S deposition and the related methods in improving the performance of lithium–sulfur batteries. Abstract : Lithium–sulfur batteries (LSBs) have received intensive attention in recent years due to their high theoretical energy density derived from the lithiation of sulfur. In the discharge process, sulfur transforms into lithium polysulfides (LiPSs) that dissolve in liquid electrolytes and then into insoluble Li2 S precipitated on the electrode surface. The electronically and ionically insulating Li2 S leads to two critical issues, including the sluggish reaction kinetics from LiPSs to Li2 S and the passivation of the electrode. In this regard, controlling the Li2 S deposition is significant for improving the performance of LSBs. In this perspective, we have summarized the recent achievements in regulating the Li2 S deposition to enhance the performance of LSBs, including the solution-mediated growth of Li2 S, sulfur host enhanced nucleation and catalysis induced kinetic improvement. Moreover, the challenges and possibilities for future research studies are discussed, highlighting the significance of regulating the Li2 S deposition to realize the high electrochemical performance and promote the practical uses of LSBs.